2008
DOI: 10.1016/j.pain.2007.06.018
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the effect of waiting for treatment for chronic pain

Abstract: In many countries timely access to care is a growing problem. As medical costs escalate health care resources must be prioritized. In this context there is an increasing need for benchmarks and best practices in wait-time management. The Canadian Pain Society struck a Task Force in December 2005 to identify benchmarks for acceptable wait-times for treatment of chronic pain. As part of the mandate a systematic review of the literature regarding the relationship between waiting times, health status and health ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
201
1
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 251 publications
(212 citation statements)
references
References 42 publications
5
201
1
5
Order By: Relevance
“…In two studies of patients being treated at an urban multidisciplinary pain centre in Denmark, no differences were seen after four months of waiting, 32 but when patients waited six months, health-related QoL, anxiety, and depression scores deteriorated. 33 These results are consistent with a systematic review 34 that found patients experiencing a reduction in health-related QoL and psychological well-being while waiting six months from the time of referral to treatment for chronic pain. 35 Like any other study, the present one has a certain number of limitations.…”
Section: Discussionsupporting
confidence: 84%
“…In two studies of patients being treated at an urban multidisciplinary pain centre in Denmark, no differences were seen after four months of waiting, 32 but when patients waited six months, health-related QoL, anxiety, and depression scores deteriorated. 33 These results are consistent with a systematic review 34 that found patients experiencing a reduction in health-related QoL and psychological well-being while waiting six months from the time of referral to treatment for chronic pain. 35 Like any other study, the present one has a certain number of limitations.…”
Section: Discussionsupporting
confidence: 84%
“…The emotional toll exacted by chronic pain is well reported, with multiple studies noting the association between chronic pain and depression, anxiety, and loss of one's social role. 1,5,6,22 PCPs frequently expressed frustration and concern in their questions to specialists, a finding that is likewise reflected in the literature. 23,24 One study found that nearly three quarters of PCPs considered providing chronic pain care to be a major source of frustration.…”
Section: Discussionmentioning
confidence: 76%
“…Long waits to access pain management and lack of access to addiction medicine and integrative and mental health specialists are barriers in CP management. 6,13 Reimbursement policies may limit patient-centered care, as PCPs have limited time for planning, performing comprehensive assessments, and coordinating care. 3 Further, there may be little teamwork or few structured opportunities for communication between office staff and PCPs, resulting in important information divulged by patients to staff, which is then not relayed to PCPs.…”
mentioning
confidence: 99%